Zur Pragmatik von Fachsprachen am Beispiel der „Anstandsliteratur“ - Peter Ernst (Linguistische Treffen in Wrocław, 2022)
Specialized languages make special demands on linguistics. Originating in the 1960s and 1970s, there is still no general consensus on the content and methods of technical language research. Current research designs combine systems linguistic, cognitive and pragmatic approaches. In terms of system linguistics, the main focus is on vocabulary; cognitive is the basis of knowledge about the real world and its linguistic coding; pragmatics looks at the circumstances of communication. This paper addresses this problem by examining the text type “decency literature” more closely. This type of communication is subject to special conditions in that a “teacher” passes on his or her competencies on etiquette to an interested target group. In addition to a book for a general audience, the technical language component is particularly emphasized by the choice of three subject-specific propriety teachings (explicitly for use in law firms, management consultants and trainees). All of them operate under the name „Knigge“, which is the reason to combine them into one corpus. The analysis shows that the four works differ considerably from one another. They do not use any special vocabulary or idiosyncratic syntactic structures, but very well different communication conditions. With the exception of the general work, it is more of a „career guide“ rather than a code of behavior. Nevertheless, they can be referred to as technical language in a cognitive and pragmatic sense, since they deal with a specific “subject”. However, they do not represent a closed system in that they are open to innovations and specific suggestions from the authors. The “compliment” is only mentioned explicitly in one work. In this sense, they are not only map fields of action, but also construct part of social reality yourself through their suggestions.